Self-vibration of thin plate band with non-linear functionally graded material - Wirowski, A. (Archives of Mechanics, 2012)
The subject of this paper is the analysis of free vibration of a thin plate band made of nonlinear functionally graded material. The considered material has periodic properties in one direction and slow but non-linear functionally graded properties in the other. The main attention is given to description of the effect of the material distribution on the overall response of the composite. The modelling approach is based on the tolerance averaging of the equation of motion. The general results are illustrated by the free vibration analysis of the bracket and the plate band simply supported on both sides.